Differences and similarities in personality functioning across different types of eating disorders - Rohde, Jens; Obbarius, Alexander; Voigt, Barbara; Sarrar, Lea; Biesenthal-Matthes, Silke; Kind, Clara-Sophia; Rose, Matthias; Hofmann, Tobias (Frontiers in Psychiatry, 2023)
Objective The classification of anorexia nervosa (AN) into subtypes is relevant due to their different symptomatology. However, subtypes (restricting type: AN-R; purging type: AN-P) differ also in terms of their personality functioning. Knowledge about these differences would allow for better treatment stratification. A pilot study indicated differences in structural abilities that can be assessed by the operationalized psychodynamic diagnosis (OPD) system. The aim of this study was therefore to systematically explore differences in personality functioning and personality between the two AN subtypes and bulimia nervosa (BN) using three personality (functioning) constructs. Methods A total of N = 110 inpatients with AN-R (n = 28), AN-P (n = 40), or BN (n = 42) were recruited in three clinics for psychosomatic medicine. Assignment to the three groups was performed using a comprehensive questionnaire validated for diagnostic purposes (Munich-ED-Quest). Personality functioning was examined using OPD Structure Questionnaire (OPD-SQ), personality by using the Personality Inventory for DSM-5–Brief Form and Big Five Inventory-10. (M)ANOVAs were used to examine differences across eating disorder groups. In addition, correlation and regression analyses were conducted. Results We observed differences on several sub- and main scales of the OPD-SQ. Whereas patients with BN showed the lowest levels, AN-R patients displayed the highest levels of personality functioning. On some sub- and main scales, such as “affect tolerance,” the subtypes of AN differed from BN, whereas on the scale “affect differentiation,” AN-R, differed from the other two groups. The total eating disorder pathology score of the Munich-ED-Quest best predicted overall personality structure [stand. β = 0.650; t(104) = 6.666; p < 0.001] and self-regulation [stand. β = 0.449; t(104) = 3.628; p < 0.001]. Discussion Our findings confirm most of the results of the pilot study. These findings can facilitate the development of stratified treatment approaches for eating disorders.